Natalizumab promotes anti-inflammatory and repair effects in multiple sclerosis - Lereim, Ragnhild Reehorst; Nytrova, Petra; Guldbrandsen, Astrid; Havrdova, Eva Kubala; Myhr, Kjell-Morten; Barsnes, Harald; Berven, Frode S (PloS one, 2024)
BACKGROUND: Multiple sclerosis is an inflammatory and degenerative disease of the central nervous system leading to demyelination and axonal loss. Relapsing-remitting multiple sclerosis (RRMS) is commonly treated by anti-inflammatory drugs, where one of the most effective drugs to date is the monoclonal antibody natalizumab. METHODS: The cerebrospinal fluid (CSF) proteome was analyzed in 56 patients with RRMS before and after natalizumab treatment, using label-free mass spectrometry and a subset of the changed proteins were verified by parallel reaction monitoring in a new cohort of 20 patients, confirming the majority of observed changes. RESULTS: A total of 287 differentially abundant proteins were detected including (i) the decrease of proteins with roles in immunity, such as immunoglobulin heavy constant mu, chitinase-3-like protein 1 and chitotriosidase, (ii) an increase of proteins involved in metabolism, such as lactate dehydrogenase A and B and malate-dehydrogenase cytoplasmic, and (iii) an increase of proteins associated with the central nervous system, including lactadherin and amyloid precursor protein. Comparison with the CSF-PR database provided evidence that natalizumab counters protein changes commonly observed in RRMS. Furthermore, vitamin-D binding protein and apolipoprotein 1 and 2 were unchanged during treatment with natalizumab, implying that these may be involved in disease activity unaffected by natalizumab. CONCLUSIONS: Our study revealed that some of the previously suggested biomarkers for MS were affected by the natalizumab treatment while others were not. Proteins not previously suggested as biomarkers were also found affected by the treatment. In sum, the results provide new information on how the natalizumab treatment impacts the CSF proteome of MS patients, and points towards processes affected by the treatment. These findings ought to be explored further to disclose potential novel disease mechanisms and predict treatment responses.
Keywords: Immunologic Factors; proteom; Proteome; Anti-Inflammatory Agents; imunologické faktory; Multiple Sclerosis, Relapsing-Remitting; Humans; biologické markery; relabující-remitující roztroušená skleróza; roztroušená skleróza; lidé; antiflogistika; Biomarkers; Multiple Sclerosis; natalizumab; Natalizumab